High-hardness galvanized sheet and preparation method thereof

By using a specific proportion of nano-coated coating composition and optimized steel plate composition on the galvanized plate, combining hot-dip galvanizing, passivation treatment and multi-step preparation methods of nano-coated galvanized plates, the shortcomings in coating uniformity, adhesion and anti-aging properties of nano-coated galvanized plates are solved, and the high performance and long life of high-hardness galvanized plates are achieved.

CN119505635AInactive Publication Date: 2025-02-25KUNSHAN FUWEI METAL PROD CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411645497.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing nano-coated galvanized plates have shortcomings in coating uniformity, adhesion and anti-aging properties, resulting in a shortened service life.

Method used

The nanocoated coating compositions of specific proportions are adopted, including silica, zinc oxide, aluminum tripolyphosphate, 1-methylhydantoin-2-imide, tert-butylsulfonamide, polystyrene-acrylate, etc., combined with the optimization of steel plate composition, the uniformity, adhesion and anti-aging properties of the coating are improved through hot-dip galvanizing, passivation treatment and multi-step preparation methods of nanocoating.

Benefits of technology

It significantly improves the coating uniformity, adhesion and anti-aging properties of nano-coated galvanized plates, extends service life, and maintains good performance in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005139599230000121
    Figure BDA0005139599230000121
  • Figure BDA0005139599230000131
    Figure BDA0005139599230000131
Patent Text Reader

Abstract

The invention relates to a high-hardness galvanized plate and a preparation method thereof, and belongs to the technical field of galvanized plates. The nano coating of the high-hardness galvanized sheet with the nano coating comprises the following components: silicon dioxide, zinc oxide, aluminum triphosphate, 1-methyl hydantoin-2-imide, tert-butyl sulfonamide, polystyrene-acrylic acid allyl ester, epoxy resin, polyurethane resin and the like. All the components are matched for use according to a specific proportion, so that the coating has good coating homogeneity, good adhesive force and outstanding corrosion resistance and aging resistance, and the service life of the nano-coating galvanized sheet can be effectively prolonged; the designed steel plate components have high hardness and good use performance, and the service life can be well prolonged when the steel plate components are matched with a plating layer and a coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of galvanized sheets, and particularly relates to a high-hardness galvanized sheet and a preparation method thereof. Background Art

[0002] Among many metal materials, galvanized sheet has been widely used in construction, automobiles, home appliances and other fields due to its good corrosion resistance, processing performance and cost-effectiveness.

[0003] Galvanized sheet is a product obtained by hot-dip galvanizing ordinary steel sheet. The galvanized layer can form a protective film on the surface of the steel sheet to prevent the steel sheet from chemically reacting with oxygen, moisture, etc. in the external environment, thereby effectively improving the corrosion resistance of the steel sheet. In the construction field, galvanized sheet is often used in roofs, walls and other parts, and can withstand the test of various climatic conditions; in the automotive industry, galvanized sheet can be used to manufacture car bodies, chassis and other parts to enhance the corrosion resistance and service life of the car; in the field of home appliances, galvanized sheet is used to manufacture refrigerators, washing machines, 3C products and other shells and internal parts, which are both beautiful and durable.

[0004] Although galvanized sheet has many advantages, its corrosion resistance still needs to be improved in some harsh environments. For example, in the marine environment, due to the large amount of salt and moisture in the air, galvanized sheet is prone to corrosion, resulting in a shortened service life. In addition, in some industrial environments, such as chemical and petroleum industries, galvanized sheet is also corroded by strong acids, alkalis and other chemicals. In order to solve these problems, researchers began to explore ways to add nano-coatings to the surface of galvanized sheet.

[0005] Nanomaterials have unique physical, chemical and mechanical properties, such as small size effect, surface effect, quantum size effect, etc. The application of nanomaterials in the field of coatings can significantly improve the performance of coatings. For galvanized sheets, nano coatings further enhance their corrosion resistance, wear resistance, scratch resistance, etc. on the basis of the galvanized layer. However, at present, the composition and technology of nano coatings are diverse, and the effects produced are also mixed. There are also the following problems:

[0006] 1. Difficult to ensure uniform coating: At the nanoscale, it is a challenge to achieve uniform distribution of coating on the surface of complex shaped objects. Due to the extremely small size of nanoparticles, they are easily affected by factors such as surface tension and airflow during the coating process, resulting in uneven coating thickness, which will affect the performance consistency of the product.

[0007] 2. Adhesion problem: The adhesion between nano coating and substrate material is often not ideal. Although nano materials have high specific surface area and activity, this also makes their bonding with the substrate relatively weak. During use, the coating will fall off due to external forces, temperature changes, chemical corrosion and other factors, reducing the service life and protective effect of the coating.

[0008] 3. Anti-aging needs to be improved: Although the nano coating may show excellent performance in the initial stage, its performance will gradually decline with the passage of time and changes in the use environment.

[0009] Therefore, it is necessary to continuously develop and improve nano-coated galvanized sheet technology to achieve high performance and long life. Summary of the invention

[0010] The existing nano-coated galvanized sheets have the problems of difficult to ensure coating uniformity, poor adhesion, and the need to improve anti-aging. The present invention provides a high-hardness galvanized sheet and a preparation method thereof. The coating components of the nano-coating include silicon dioxide, zinc oxide, aluminum tripolyphosphate, 1-methylhydantoin-2-imide, tert-butylsulfonamide, polystyrene-acrylate, etc.; each component is used in combination according to a specific proportion, and has good coating homogeneity, good adhesion, outstanding corrosion resistance and aging resistance, and can effectively extend the service life of the nano-coated galvanized sheet; the steel plate component is also designed to have high hardness and good performance, and can be well matched with the plating and coating to extend the service life. The specific technical scheme is as follows:

[0011] A high-hardness galvanized sheet (the high-hardness galvanized sheet can be named FW500), comprising a steel sheet, a galvanized layer and a nano coating, wherein the thickness of the galvanized layer is 4 μm to 80 μm; the thickness of the nano coating is 3 μm to 40 μm; the coating of the nano coating comprises the following raw materials in parts by mass: 10 to 15 parts of silicon dioxide, 5 to 10 parts of zinc oxide, 5 to 10 parts of aluminum tripolyphosphate, 1 to 3 parts of 1-methylhydantoin-2-imide, 1 to 3 parts of tert-butyl sulfonamide, 1 to 3 parts of polystyrene-acrylate, 20 to 25 parts of epoxy resin, 20 to 25 parts of polyurethane resin, 2 to 5 parts of leveling agent, 1 to 3 parts of defoaming agent, and 30 to 50 parts of ethyl acetate.

[0012] In the above technical solution, the silicon dioxide, zinc oxide and aluminum tripolyphosphate are all nano-sized particles, and the particle size is less than 100 nm.

[0013] In the above technical solution, the steel plate composition is: carbon 0.03wt%~0.15wt%, manganese 0.2wt%~0.5wt%, silicon 0.1wt%~0.3wt%, phosphorus ≤0.03wt%, sulfur ≤0.02wt%, and the remainder is iron and unavoidable impurities.

[0014] In the above technical solution, the leveling agent is SIF-720 leveling agent; the defoaming agent is BYK-A555 defoaming agent.

[0015] The above-mentioned method for preparing a high-hardness galvanized sheet comprises the following steps:

[0016] S1, substrate pretreatment:

[0017] The steel plate is cleaned with a sodium carbonate aqueous solution to remove oil stains on the surface of the steel plate, and then the steel plate is rinsed with clean water to remove the residual sodium carbonate aqueous solution; the steel plate is cleaned with a dilute hydrochloric acid aqueous solution to remove rust and scale on the surface of the steel plate, and then the steel plate is rinsed with clean water to remove the residual dilute hydrochloric acid aqueous solution, and after drying, a clean steel plate is obtained;

[0018] S2, hot dip galvanizing:

[0019] The clean steel sheet is immersed in zinc liquid for hot-dip galvanizing treatment, and the galvanized sheet is cooled to room temperature by air cooling to obtain a galvanized sheet;

[0020] S3, passivation treatment:

[0021] The galvanized sheet is immersed in a passivation solution for passivation treatment, the galvanized sheet is taken out, the passivation solution remaining on the surface is washed off with clean water, and after drying, a passivated galvanized sheet is obtained;

[0022] S4, Nano coating:

[0023] The coating is applied on the surface of the passivated galvanized sheet, and after curing and drying, a nano-coated galvanized sheet is obtained.

[0024] In S1 of the above preparation method, the concentration of the sodium carbonate aqueous solution is 3wt% to 5wt%, and the temperature of the sodium carbonate aqueous solution is 40°C to 60°C; the concentration of the dilute hydrochloric acid aqueous solution is 6wt% to 8wt%, and the temperature of the dilute hydrochloric acid aqueous solution is 30°C to 40°C.

[0025] In S2 of the above preparation method, the parameters of the hot-dip galvanizing treatment are: the temperature of the zinc solution is 450° C. to 460° C., the immersion time is 2s to 5s, and the withdrawal speed is 1m / min to 5m / min.

[0026] In S3 of the above preparation method, the components of the passivation solution are: chromic anhydride 5g / L~10g / L, sulfuric acid 1g / L~5g / L, nitric acid 1g / L~3g / L, and the solvent is water.

[0027] In S3 of the above preparation method, the parameters of the passivation treatment are: the temperature of the passivation solution is 30° C. to 40° C., and the immersion time is 10 s to 60 s.

[0028] In S4 of the above preparation method, the coating is applied on the surface of the passivated galvanized sheet by roller coating.

[0029] The present invention provides a high-hardness galvanized sheet and a preparation method thereof, and the beneficial effects are:

[0030] 1. The coating components of the nano coating of the present invention include silicon dioxide, zinc oxide, aluminum tripolyphosphate, 1-methylhydantoin-2-imide, tert-butylsulfonamide, polystyrene-propylene acrylate, epoxy resin, polyurethane resin, leveling agent, defoaming agent, and ethyl acetate. The components are used in combination according to a specific ratio, and the coating has good homogeneity, good adhesion, outstanding corrosion resistance and aging resistance, and can effectively extend the service life of the nano coating galvanized sheet.

[0031] 2. Nano-silicon dioxide has a three-dimensional network structure and a large specific surface area, and there are a large number of active groups such as hydroxyl groups on the surface. These hydroxyl groups can form hydrogen bonds and other chemical bonds with the polymer molecules in the coating, thereby enhancing the interaction with the polymer. Nano-silicon dioxide particles can fill the pores in the coating, making the coating denser, thereby improving the shear force and peeling force of the coating, enhancing the adhesion and hardness of the coating, and improving the scratch resistance of the coating. It has excellent ultraviolet absorption and infrared reflection properties, which can effectively reduce the color difference value of the coating caused by ultraviolet and infrared radiation, improve the weather resistance of the coating, and maintain the stability of the color. It can improve the thixotropy of the coating, so that the coating has good rheological properties during construction, prevent sagging, and facilitate construction.

[0032] 3. The grain size of nano zinc oxide is refined, which changes the electronic structure and crystal structure of its surface, resulting in surface effects, volume effects, quantum size effects and macro tunneling effects that macroscopic objects do not have. These special effects make nano zinc oxide have unique properties in optics, electricity, chemistry and other aspects, thus playing a variety of roles in coatings. Nano zinc oxide has excellent shielding ability against ultraviolet rays. Adding it to the coating can effectively block the damage of ultraviolet rays to the coating and substrate, improve the anti-aging performance of the coating, and extend the service life. And because of its nano characteristics, large specific surface area and high chemical activity, it can better cooperate with other pigments to improve the dispersibility and stability of the pigment.

[0033] 4. Aluminum tripolyphosphate is an important anti-rust filler that can form a dense protective film on the metal surface to prevent oxygen, moisture and other corrosive substances from contacting the metal, thereby playing an anti-rust and anti-corrosion role. It is widely used in nano-coatings such as water-based epoxy anti-corrosion coatings and can significantly improve the anti-corrosion performance of coatings. Aluminum tripolyphosphate releases phosphate ions during the hydrolysis process. These ions can react with iron ions on the metal surface to form insoluble phosphate precipitation, thereby forming a stable protective film on the metal surface. In addition, nano-scale aluminum tripolyphosphate has a small particle size and a large specific surface area, which can be better adsorbed on the metal surface and enhance the anti-corrosion effect.

[0034] 5. Epoxy resin has excellent bonding properties and can firmly bond with the substrate, providing good adhesion for the coating. In nano coatings, epoxy resin can firmly bond nanoparticles together to form a stable coating. Polyurethane resin has good flexibility and elasticity, which can give the coating excellent flexibility and bending resistance, making the coating less likely to crack and peel off when subjected to external forces; it has high wear resistance, improves the wear resistance of the coating, and extends the service life of the coating.

[0035] 6. 1-Methylhydantoin-2-imide can help stabilize other ingredients and ensure that the coating maintains performance stability under various environmental conditions. It has a certain anti-aging effect, can help improve the anti-aging ability of the nano coating, and extend the service life of the nano coating galvanized sheet. When the coating is exposed to the air for a long time, it can reduce the performance degradation caused by aging.

[0036] 7. Tert-butyl sulfonamide can enhance the adhesion between the nano coating and the galvanized sheet. The surface of the galvanized sheet is usually smooth. After adding tert-butyl sulfonamide, it can improve the interface bonding between the coating and the substrate, so that the nano coating can be better attached to the galvanized sheet and not easy to fall off. It will participate in the curing reaction and other chemical reactions of the nano coating, thereby changing the chemical structure and physical properties of the coating.

[0037] 8. Polystyrene-propylene acrylate is a film-forming substance that can form a uniform and continuous film on the surface of the galvanized sheet. This is crucial to the integrity and protective performance of the nano coating, and can effectively block the corrosion of the galvanized sheet by external moisture, oxygen, corrosive substances, etc. This substance can increase the flexibility of the nano coating, so that the coating can better adapt to the deformation and stress that can be generated during the processing and use of the galvanized sheet, and avoid cracking and damage to the coating.

[0038] 9. The stabilizing effect of 1-methylhydantoin-2-imide, the adhesion enhancing effect of tert-butylsulfonamide, and the film-forming and flexibility improving effects of polystyrene-propylene acrylate can cooperate with each other to improve the comprehensive performance of the nano-coating from multiple aspects, so that the nano-coated galvanized sheet has better corrosion resistance, wear resistance, and aging resistance. The three together will affect the microstructure of the nano-coating, making the coating more dense and uniform. Under different environmental conditions, the synergistic effect of these three components can make the nano-coated galvanized sheet have better adaptability. Whether in harsh environments such as high temperature, low temperature, and humidity, or under mechanical stress, the coating can maintain good performance and extend the service life of the galvanized sheet.

[0039] 10. After the galvanized layer is passivated, the passivation treatment can form a dense passivation film on the surface of the galvanized layer. This film can improve the surface properties of the galvanized layer and make it easier for the nano coating to adhere to it. The passivation film provides an interface that is more suitable for the adhesion of the nano coating and increases the bonding force between the two. The passivation treatment itself can improve the anti-corrosion performance of the galvanized sheet, and coating the nano coating on the passivated galvanized layer is equivalent to adding another layer of protection on the basis of anti-corrosion. The nano coating can further block the intrusion of corrosive substances and work together with the passivation layer to greatly improve the anti-corrosion ability of the nano coating galvanized sheet. The surface of the galvanized layer after passivation treatment is more uniform and smooth, which is conducive to the uniform coating of the nano coating. It can reduce defects and unevenness in the coating, making the performance of the nano coating more stable and reliable.

[0040] 11. The steel sheet of the present invention has the following components: carbon 0.03wt% to 0.15wt%, manganese 0.2wt% to 0.5wt%, silicon 0.1wt% to 0.3wt%, phosphorus ≤ 0.03wt%, sulfur ≤ 0.02wt%, and the remainder is iron and unavoidable impurities. The galvanized sheet has high hardness and good performance, and can be well matched with the plating layer and the coating to extend the service life. DETAILED DESCRIPTION

[0041] The present invention is further described below in conjunction with specific implementation cases, but the present invention is not limited to these embodiments.

[0042] Example 1

[0043] A high-hardness galvanized sheet comprises a steel sheet, a galvanized layer and a nano coating, wherein the steel sheet comprises: 0.1wt% carbon, 0.3wt% manganese, 0.2wt% silicon, 0.02wt% phosphorus, 0.01wt% sulfur, and the remainder is iron and inevitable impurities; the galvanized layer has a thickness of 50μm; the nano coating has a thickness of 25μm; and the coating of the nano coating comprises the following raw materials in parts by mass: 12 parts of silicon dioxide, 8 parts of zinc oxide, 8 parts of aluminum tripolyphosphate, 2 parts of 1-methylhydantoin-2-imide, 2 parts of tert-butylsulfonamide, 2 parts of polystyrene-acrylic acid acrylate, 22 parts of epoxy resin, 24 parts of polyurethane resin, 3 parts of SIF-720 leveling agent, 2 parts of BYK-A555 defoaming agent, and 40 parts of ethyl acetate.

[0044] The above-mentioned method for preparing a high-hardness galvanized sheet comprises the following steps:

[0045] S1, substrate pretreatment:

[0046] A 2 mm thick steel plate is cleaned with a sodium carbonate aqueous solution at a temperature of 50°C and a concentration of 4wt% to remove oil stains on the surface of the steel plate, and then the steel plate is rinsed with clean water to remove the residual sodium carbonate aqueous solution; a 35°C 7wt% dilute hydrochloric acid aqueous solution is used to clean the steel plate to remove rust and scale on the surface of the steel plate, and then the steel plate is rinsed with clean water to remove the residual dilute hydrochloric acid aqueous solution, and then dried to obtain a clean steel plate;

[0047] S2, hot dip galvanizing:

[0048] The clean steel sheet is immersed in zinc liquid for hot-dip galvanizing treatment. The parameters of hot-dip galvanizing treatment are: the temperature of zinc liquid is 455°C, the immersion time is 3s, and the withdrawal speed is 3m / min; the galvanized sheet is cooled to room temperature by air cooling to obtain a galvanized sheet;

[0049] S3, passivation treatment:

[0050] The galvanized sheet was immersed in the passivation solution for passivation treatment. The parameters of the passivation treatment were as follows: the temperature of the passivation solution was 35°C and the immersion time was 30s. The galvanized sheet was taken out, and the passivation solution remaining on the surface was washed off with clean water. After drying, a passivated galvanized sheet was obtained.

[0051] The composition of the passivation solution is: chromic anhydride 8g / L, sulfuric acid 3g / L, nitric acid 2g / L, and the solvent is water;

[0052] S4, Nano coating:

[0053] The coating was applied on the surface of the passivated galvanized sheet by roller coating, cured at 160° C. for 40 min, and dried to obtain a nano-coated galvanized sheet.

[0054] Example 2

[0055] A high-hardness galvanized sheet comprises a steel sheet, a galvanized layer and a nano coating, wherein the steel sheet comprises: 0.03wt% carbon, 0.2wt% manganese, 0.1wt% silicon, 0.01wt% phosphorus, 0.01wt% sulfur, and the remainder is iron and inevitable impurities; the galvanized layer has a thickness of 4μm; the nano coating has a thickness of 16μm; and the coating of the nano coating comprises the following raw materials in parts by mass: 10 parts of silicon dioxide, 5 parts of zinc oxide, 5 parts of aluminum tripolyphosphate, 1 part of 1-methylhydantoin-2-imide, 1 part of tert-butylsulfonamide, 1 part of polystyrene-acrylic acid acrylate, 20 parts of epoxy resin, 20 parts of polyurethane resin, 2 parts of SIF-720 leveling agent, 1 part of BYK-A555 defoaming agent, and 30 parts of ethyl acetate.

[0056] The above-mentioned method for preparing a high-hardness galvanized sheet comprises the following steps:

[0057] S1, substrate pretreatment:

[0058] A 2 mm thick steel plate is cleaned with a sodium carbonate aqueous solution at a temperature of 40°C and a concentration of 3wt% to remove oil stains on the surface of the steel plate, and then the steel plate is rinsed with clean water to remove the residual sodium carbonate aqueous solution; a 30°C and 6wt% dilute hydrochloric acid aqueous solution is used to clean the steel plate to remove rust and scale on the surface of the steel plate, and then the steel plate is rinsed with clean water to remove the residual dilute hydrochloric acid aqueous solution, and after drying, a clean steel plate is obtained;

[0059] S2, hot dip galvanizing:

[0060] The clean steel sheet is immersed in zinc liquid for hot-dip galvanizing treatment. The parameters of hot-dip galvanizing treatment are: the temperature of zinc liquid is 450°C, the immersion time is 2s, and the withdrawal speed is 1m / min; the galvanized sheet is cooled to room temperature by air cooling to obtain a galvanized sheet;

[0061] S3, passivation treatment:

[0062] The galvanized sheet was immersed in the passivation solution for passivation treatment. The parameters of the passivation treatment were: the temperature of the passivation solution was 30°C and the immersion time was 10s. The galvanized sheet was taken out, and the passivation solution remaining on the surface was washed off with clean water. After drying, a passivated galvanized sheet was obtained.

[0063] The composition of the passivation solution is: chromic anhydride 5g / L, sulfuric acid 1g / L, nitric acid 1g / L, and the solvent is water;

[0064] S4, Nano coating:

[0065] The coating was applied on the surface of the passivated galvanized sheet by roller coating, cured at 170° C. for 30 min, and dried to obtain a nano-coated galvanized sheet.

[0066] Example 3

[0067] A high-hardness galvanized sheet comprises a steel sheet, a galvanized layer and a nano coating, wherein the steel sheet comprises: 0.08wt% carbon, 0.5wt% manganese, 0.1wt% silicon, 0.03wt% phosphorus, 0.01wt% sulfur, and the remainder is iron and inevitable impurities; the thickness of the galvanized layer is 30μm; the thickness of the nano coating is 40μm; the coating of the nano coating comprises the following raw materials in parts by mass: 10 parts of silicon dioxide, 10 parts of zinc oxide, 5 parts of aluminum tripolyphosphate, 3 parts of 1-methylhydantoin-2-imide, 1 part of tert-butylsulfonamide, 3 parts of polystyrene-acrylic acid acrylate, 20 parts of epoxy resin, 25 parts of polyurethane resin, 2 parts of SIF-720 leveling agent, 3 parts of BYK-A555 defoaming agent, and 30 parts of ethyl acetate.

[0068] The above-mentioned method for preparing a high-hardness galvanized sheet comprises the following steps:

[0069] S1, substrate pretreatment:

[0070] A 2 mm thick steel plate is cleaned with a sodium carbonate aqueous solution at a temperature of 60°C and a concentration of 3 wt% to remove oil stains on the surface of the steel plate, and then the steel plate is rinsed with clean water to remove the residual sodium carbonate aqueous solution; a 40°C and 6 wt% dilute hydrochloric acid aqueous solution is used to clean the steel plate to remove rust and scale on the surface of the steel plate, and then the steel plate is rinsed with clean water to remove the residual dilute hydrochloric acid aqueous solution, and then dried to obtain a clean steel plate;

[0071] S2, hot dip galvanizing:

[0072] The clean steel sheet is immersed in zinc liquid for hot-dip galvanizing treatment. The parameters of hot-dip galvanizing treatment are: the temperature of zinc liquid is 460°C, the immersion time is 2s, and the withdrawal speed is 5m / min; the galvanized sheet is cooled to room temperature by air cooling to obtain a galvanized sheet;

[0073] S3, passivation treatment:

[0074] The galvanized sheet was immersed in the passivation solution for passivation treatment. The parameters of the passivation treatment were as follows: the temperature of the passivation solution was 30°C and the immersion time was 60s. The galvanized sheet was taken out, and the passivation solution remaining on the surface was washed off with clean water. After drying, a passivated galvanized sheet was obtained.

[0075] The composition of the passivation solution is: chromic anhydride 5g / L, sulfuric acid 5g / L, nitric acid 1g / L, and the solvent is water;

[0076] S4, Nano coating:

[0077] The coating was applied on the surface of the passivated galvanized sheet by roller coating, cured at 160° C. for 25 min, and dried to obtain a nano-coated galvanized sheet.

[0078] Example 4

[0079] A high-hardness galvanized sheet comprises a steel sheet, a galvanized layer and a nano coating, wherein the steel sheet comprises: 0.15wt% carbon, 0.5wt% manganese, 0.3wt% silicon, 0.01wt% phosphorus, 0.02wt% sulfur, and the remainder is iron and inevitable impurities; the thickness of the galvanized layer is 80μm; the thickness of the nano coating is 40μm; the coating of the nano coating comprises the following raw materials in parts by mass: 15 parts of silicon dioxide, 10 parts of zinc oxide, 10 parts of aluminum tripolyphosphate, 3 parts of 1-methylhydantoin-2-imide, 3 parts of tert-butylsulfonamide, 3 parts of polystyrene-acrylic acid acrylate, 25 parts of epoxy resin, 25 parts of polyurethane resin, 5 parts of SIF-720 leveling agent, 3 parts of BYK-A555 defoaming agent, and 50 parts of ethyl acetate.

[0080] The above-mentioned method for preparing a high-hardness galvanized sheet comprises the following steps:

[0081] S1, substrate pretreatment:

[0082] A 2 mm thick steel plate is cleaned with a sodium carbonate aqueous solution at a temperature of 60°C and a concentration of 5wt% to remove oil stains on the surface of the steel plate, and then the steel plate is rinsed with clean water to remove the residual sodium carbonate aqueous solution; a 40°C 8wt% dilute hydrochloric acid aqueous solution is used to clean the steel plate to remove rust and scale on the surface of the steel plate, and then the steel plate is rinsed with clean water to remove the residual dilute hydrochloric acid aqueous solution, and then dried to obtain a clean steel plate;

[0083] S2, hot dip galvanizing:

[0084] The clean steel sheet is immersed in zinc liquid for hot-dip galvanizing treatment. The parameters of hot-dip galvanizing treatment are: the temperature of zinc liquid is 460°C, the immersion time is 5s, and the withdrawal speed is 5m / min; the galvanized sheet is cooled to room temperature by air cooling to obtain a galvanized sheet;

[0085] S3, passivation treatment:

[0086] The galvanized sheet was immersed in the passivation solution for passivation treatment. The parameters of the passivation treatment were as follows: the temperature of the passivation solution was 40°C and the immersion time was 60s. The galvanized sheet was taken out, and the passivation solution remaining on the surface was washed off with clean water. After drying, a passivated galvanized sheet was obtained.

[0087] The composition of the passivation solution is: chromic anhydride 10g / L, sulfuric acid 5g / L, nitric acid 3g / L, and the solvent is water;

[0088] S4, Nano coating:

[0089] The coating was applied on the surface of the passivated galvanized sheet by roller coating, cured at 150° C. for 40 min, and dried to obtain a nano-coated galvanized sheet.

[0090] Example 5

[0091] A high-hardness galvanized sheet comprises a steel sheet, a galvanized layer and a nano coating, wherein the steel sheet comprises: 0.15wt% carbon, 0.2wt% manganese, 0.3wt% silicon, 0.03wt% phosphorus, 0.02wt% sulfur, and the remainder is iron and inevitable impurities; the galvanized layer has a thickness of 60μm; the nano coating has a thickness of 3μm; and the coating of the nano coating comprises the following raw materials in parts by mass: 15 parts of silicon dioxide, 5 parts of zinc oxide, 10 parts of aluminum tripolyphosphate, 1 part of 1-methylhydantoin-2-imide, 3 parts of tert-butylsulfonamide, 1 part of polystyrene-acrylic acid acrylate, 25 parts of epoxy resin, 20 parts of polyurethane resin, 5 parts of SIF-720 leveling agent, 1 part of BYK-A555 defoaming agent, and 50 parts of ethyl acetate.

[0092] The above-mentioned method for preparing a high-hardness galvanized sheet comprises the following steps:

[0093] S1, substrate pretreatment:

[0094] A 2 mm thick steel plate is cleaned with a sodium carbonate aqueous solution at a temperature of 40°C and a concentration of 5wt% to remove oil stains on the surface of the steel plate, and then the steel plate is rinsed with clean water to remove the residual sodium carbonate aqueous solution; a 30°C 8wt% dilute hydrochloric acid aqueous solution is used to clean the steel plate to remove rust and scale on the surface of the steel plate, and then the steel plate is rinsed with clean water to remove the residual dilute hydrochloric acid aqueous solution, and then dried to obtain a clean steel plate;

[0095] S2, hot dip galvanizing:

[0096] The clean steel sheet is immersed in zinc liquid for hot-dip galvanizing treatment. The parameters of hot-dip galvanizing treatment are: the temperature of zinc liquid is 450°C, the immersion time is 5s, and the withdrawal speed is 1m / min; the galvanized sheet is cooled to room temperature by air cooling to obtain a galvanized sheet;

[0097] S3, passivation treatment:

[0098] The galvanized sheet was immersed in the passivation solution for passivation treatment. The parameters of the passivation treatment were as follows: the temperature of the passivation solution was 40°C and the immersion time was 10s. The galvanized sheet was taken out, and the passivation solution remaining on the surface was washed off with clean water. After drying, a passivated galvanized sheet was obtained.

[0099] The composition of the passivation solution is: chromic anhydride 10g / L, sulfuric acid 1g / L, nitric acid 3g / L, and the solvent is water;

[0100] S4, Nano coating:

[0101] The coating was applied on the surface of the passivated galvanized sheet by roller coating, cured at 180° C. for 20 min, and dried to obtain a nano-coated galvanized sheet.

[0102] In the above embodiments, the silicon dioxide, zinc oxide, and aluminum tripolyphosphate used are all nanometer-sized particles, and the particle size is all below 100 nm. The model of polystyrene-acrylate ester is YSG-626R, which comes from Shanghai Yuyu New Material Technology Co., Ltd.; the source of SI F-720 leveling agent is Tianjin Hepufei New Material Co., Ltd. Tert-butyl sulfonamide is 2-methylpropane-2-sulfonamide. The model of epoxy resin is E51, which comes from Shandong Jingshun Chemical Co., Ltd. The model of polyurethane resin is F0400, which comes from Shenzhen Yoshida Chemical Co., Ltd.

[0103] Comparative Example 1

[0104] The coating does not contain 1-methylhydantoin-2-imide; the content of 1-methylhydantoin-2-imide is replaced by ethyl acetate; other parameters and methods are the same as in Example 1.

[0105] Comparative Example 2

[0106] The coating does not contain tert-butylsulfonamide; the content of tert-butylsulfonamide is replaced by ethyl acetate; other parameters and methods are the same as in Example 1.

[0107] Comparative Example 3

[0108] The coating does not contain polystyrene-propylene acrylate; the content of polystyrene-propylene acrylate is replaced by ethyl acetate; other parameters and methods are the same as in Example 1.

[0109] Comparative Example 4

[0110] The coating does not contain 1-methylhydantoin-2-imide, tert-butylsulfonamide and polystyrene-propylene acrylate; the contents of 1-methylhydantoin-2-imide, tert-butylsulfonamide and polystyrene-propylene acrylate are all replaced by ethyl acetate; other parameters and methods are the same as in Example 1.

[0111] Comparative Example 5

[0112] The galvanized sheet is not subjected to passivation treatment and is directly coated with paint; other parameters and methods are the same as those in Example 1.

[0113] The corrosion resistance, adhesion and anti-aging properties of the nano-coated galvanized sheets prepared in the above-mentioned embodiments and comparative examples were tested.

[0114] (1) Corrosion resistance test: The test was conducted according to the method of GB / T 10125 "Artificial atmosphere corrosion test salt spray test", using 5% sodium chloride solution, temperature of 35°C, continuous spraying for 480 hours, and recording the time without rust. The test results are shown in Table 1.

[0115] (2) Adhesion test: The test was carried out according to the method of GB / T 9286 "Scratch test for paint and varnish films". The adhesion results are shown in Table 1.

[0116] (3) Anti-aging test: According to GB / T 23987 "Artificial weathering of paint and varnish coatings - exposure to fluorescent ultraviolet light and water", an artificial accelerated ultraviolet light aging test was used for determination. The ultraviolet light wavelength was set to 340 nm, the irradiation intensity was 0.8 W / m2, the temperature was 50°C, and the humidity was 60%. After the coating was aged for 60 days, the adhesion was tested. The yellowing resistance of the paint film was determined by a photoelectric colorimeter. The contact angle measuring instrument was used to detect the contact angle of the coating. The surface energy change rate was calculated. The surface energy change rate = (surface energy after aging - surface energy after drying) / surface energy after drying × 100%. The results are shown in Table 1.

[0117] Table 1 Test results of corrosion resistance, adhesion and anti-aging performance

[0118]

[0119]

[0120] Corrosion protection evaluation level classification:

[0121] 1-Excellent: The coating is barely affected by the salt spray, with no blistering, no rusting, almost no color change, no swelling, no peeling, and no corrosion pits.

[0122] 2-Good: The paint is slightly affected by salt spray, with a small amount of tiny bubbles, which are sparsely distributed; there are very few rust spots, which are not obvious; the color changes slightly, but it does not affect the overall appearance; there is slight swelling, which does not affect the integrity of the coating; there is no obvious flaking, and there is very little edge peeling; there are very few and very small corrosion pits.

[0123] 3-Medium: The coating is affected by salt spray to a certain extent, with a certain amount of blistering, which is widely distributed, but the size of the blister is moderate; there are a small amount of rust spots, which are relatively obvious; the color change is more obvious, but the original color can still be distinguished; there is a certain degree of swelling, and the coating becomes partially soft; there is a small amount of local peeling; there are some smaller corrosion pits.

[0124] 4-Poor: The coating is severely affected by salt spray, with a large number of bubbles of varying sizes and dense distribution; there are many large rust spots, which seriously affect the appearance; the color changes greatly, making it difficult to distinguish the original color; there is severe swelling and obvious deformation of the coating; there are many peeling areas; there are many large corrosion pits.

[0125] 5-Very Poor: The coating is completely destroyed by salt spray and loses its protective effect. The entire coating is covered with bubbles, and some bubbles have burst; there is large-scale rust and serious corrosion of the substrate; the color has completely changed and the original color cannot be recognized; the coating has completely swelled and lost its original shape; the coating has peeled off over a large area and the substrate is completely exposed; a large number of large and deep corrosion pits make the coating surface rough.

[0126] It can be seen from the above results that the nano-coated galvanized sheet of Examples 1 to 5 has good corrosion resistance, adhesion and anti-aging. From the results of Comparative Example 1, it can be seen that 1-methylhydantoin-2-imide can maintain the stability of coating performance, improve the uniformity of coating mixing, enhance anti-corrosion performance, and enhance anti-corrosion performance; 1-methylhydantoin-2-imide is not added to the coating, and the corrosion resistance and anti-aging performance of the galvanized sheet are reduced. From the results of Comparative Example 2, it can be seen that tert-butyl sulfonamide can improve the adhesion of the coating, enhance the corrosion resistance and anti-aging performance, and tert-butyl sulfonamide is not added to the coating, and the various properties of the galvanized sheet are reduced. From the results of Comparative Example 3, it can be seen that polystyrene-acrylic acid propylene ester has a film-forming effect, enhances the corrosion resistance, improves the adhesion and anti-aging performance of the coating, and polystyrene-acrylic acid propylene ester is not added to the coating, and the various properties of the galvanized sheet are reduced. From the results of comparative example 4, it can be seen that the coating does not contain 1-methylhydantoin-2-imide, tert-butylsulfonamide and polystyrene-propylene acrylate at the same time, and the corrosion resistance, adhesion and anti-aging properties of the galvanized sheet are significantly reduced. From the results of comparative example 5, it can be seen that passivation treatment can improve the coating uniformity, adhesion, corrosion resistance and anti-aging of the coating; the galvanized sheet is not passivated and the coating is directly applied, and the various properties of the galvanized sheet are reduced.

Claims

1. A high-hardness galvanized sheet, comprising a steel sheet, a galvanized layer and a nano coating, characterized in that: The thickness of the zinc-plated layer is 4 μm to 80 μm; the thickness of the nano-coating is 3 μm to 40 μm; the coating of the nano-coating comprises the following raw materials in parts by mass: 10 to 15 parts of silicon dioxide, 5 to 10 parts of zinc oxide, 5 to 10 parts of aluminum tripolyphosphate, 1 to 3 parts of 1-methylhydantoin-2-imide, 1 to 3 parts of tert-butyl sulfonamide, 1 to 3 parts of polystyrene-acrylate, 20 to 25 parts of epoxy resin, 20 to 25 parts of polyurethane resin, 2 to 5 parts of leveling agent, 1 to 3 parts of defoaming agent, and 30 to 50 parts of ethyl acetate.

2. A high hardness galvanized sheet according to claim 1, characterized in that: The silicon dioxide, zinc oxide and aluminum tripolyphosphate are all nanometer-sized particles, and the particle size is all below 100 nm.

3. The high hardness galvanized sheet according to claim 1, characterized in that: The steel plate comprises: carbon 0.03wt% to 0.15wt%, manganese 0.2wt% to 0.5wt%, silicon 0.1wt% to 0.3wt%, phosphorus ≤ 0.03wt%, sulfur ≤ 0.02wt%, and the remainder is iron and unavoidable impurities.

4. The high-hardness galvanized sheet according to claim 1, characterized in that: The leveling agent is SIF-720 leveling agent; the defoaming agent is BYK-A555 defoaming agent.

5. A method for preparing a high-hardness galvanized sheet, used for preparing a high-hardness galvanized sheet according to claim 1, characterized in that: The preparation method comprises the following steps: S1, substrate pretreatment: The steel plate is cleaned with a sodium carbonate aqueous solution to remove oil stains on the surface of the steel plate, and then the steel plate is rinsed with clean water to remove the residual sodium carbonate aqueous solution; the steel plate is cleaned with a dilute hydrochloric acid aqueous solution to remove rust and scale on the surface of the steel plate, and then the steel plate is rinsed with clean water to remove the residual dilute hydrochloric acid aqueous solution, and after drying, a clean steel plate is obtained; S2, hot dip galvanizing: The clean steel sheet is immersed in zinc liquid for hot-dip galvanizing treatment, and the galvanized sheet is cooled to room temperature by air cooling to obtain a galvanized sheet; S3, passivation treatment: The galvanized sheet is immersed in a passivation solution for passivation treatment, the galvanized sheet is taken out, the passivation solution remaining on the surface is washed off with clean water, and after drying, a passivated galvanized sheet is obtained; S4, Nano coating: The coating is applied on the surface of the passivated galvanized sheet, and after curing and drying, a nano-coated galvanized sheet is obtained.

6. The method for preparing a high-hardness galvanized sheet according to claim 5, characterized in that: In S1, the concentration of the sodium carbonate aqueous solution is 3wt% to 5wt%, and the temperature of the sodium carbonate aqueous solution is 40°C to 60°C; the concentration of the dilute hydrochloric acid aqueous solution is 6wt% to 8wt%, and the temperature of the dilute hydrochloric acid aqueous solution is 30°C to 40°C.

7. The method for preparing a high-hardness galvanized sheet according to claim 5, characterized in that: In S2, the parameters of the hot-dip galvanizing treatment are: the temperature of the zinc solution is 450°C to 460°C, the immersion time is 2s to 5s, and the withdrawal speed is 1m / min to 5m / min.

8. The method for preparing a high-hardness galvanized sheet according to claim 5, characterized in that: In S3, the components of the passivation solution are: chromic anhydride 5g / L-10g / L, sulfuric acid 1g / L-5g / L, nitric acid 1g / L-3g / L, and the solvent is water.

9. The method for preparing a high-hardness galvanized sheet according to claim 5, characterized in that: In S3, the parameters of the passivation treatment are: the temperature of the passivation solution is 30°C to 40°C, and the immersion time is 10s to 60s.

10. The method for preparing a high-hardness galvanized sheet according to claim 5, characterized in that: In S4, the coating is applied on the surface of the passivated galvanized sheet by roller coating.

Citation Information

Patent Citations

  • Protective coatings for acidic active ingredients

    CN103221038A

  • Polyaspartic acid ester paint for ground protection and decoration and preparation method thereof

    CN118496747A

  • Composite organic-coated steel sheet

    EP0573015A1

  • High corrosion resistant plural layer coated steel plate

    JP1989008034A

  • Surface treated steel sheet

    US20250206962A1